Testing and Measurement on Willingness to Use Augmented Reality, Virtual Reality, and AI-Enabled Checkouts - Junsawang, Sunisa; Chaveesuk, Singha; Chaiyasoonthorn, Wornchanok (My University, 2022)
Augmented Reality, Virtual Reality, and AI-Enabled Checkouts in several industries, including education, retail, etc. These technologies have shown an essential and highly important ability to provide customers with new innovative user experiences and interactions between humans and technology. This paper focuses on developing a tool including nine latent and 23 observed variables for an exam a conceptual framework of Willingness to Use Augmented Reality, Virtual Reality, and AI-Enabled Checkouts with Unified Theory of Acceptance and Use of Technology2, Expectation-Confirmation Model, Service Quality, and Personal Innovativeness. These findings will provide observed variables as a tool for exam insight into what affects customer willingness to use.
Keywords: AI-Enabled checkouts; augmented reality; ECM; personal innovativeness; service quality; UTAUT2; virtual reality